THYMOMA REMISSION WITH STEROID THERAPY IN MYASTHENIA GRAVES WITH GIANT THYMOMA - Şimşek, Fatma (MNJ (Malang Neurology Journal), 2024)
The thymoma is an uncommon neoplasm. It is detected incidentally in some patients. Myasthenia gravis (MG) is an autoimmune disease and closely related to thymoma. Between 10% and 20% of patients with MG have thymoma and 30%–50% of patients with thymoma have MG. Thymectomy is part of the treatment for MG patients. However, the patient must be stabilized before thymectomy. We present a 26-year-old male case with giant thymoma. In the initial evaluation of the patient, a giant-sized thymoma was observed, which was thought to cause vascular invasion.  Interestingly, the introduction of corticosteroid therapy for MG symptom management resulted in unexpected significant remission of giant thymoma. After steroid treatment, thymectomy was performed. This case demonstrated that steroid therapy was effective and well tolerated for the treatment of both thymoma and MG. Therefore, steroid therapy should be continued for a while for thymoma remission before surgery in MG patients with giant thymoma. Treatment is arranged according to the clinical findings of the patient. Each patient's response to treatment and duration of treatment may differ from each other.   After thymectomy, long-term follow-up is required for the possibility of thymoma becoming malignant.